On the Cultural Transmission of Corruption - Esther Hauk; María Sáez-Martí (The Research Institute of Industrial Economics (IUI), 2001)
We provide a cultural explanation to the phenomenon of corruption in the framework of an overlapping generations model with intergenerational transmission of values. We show that the economy has two steady states with different levels of corruption. The driving force in the equilibrium selection process is the education effort exerted by parents which depends on the distribution of ethics in the population and on expectations about future policies. We propose some policy interventions which via parents' efforts have long-lasting effects on corruption and show the success of intensive education campaigns. Educating the young is a key element in reducing corruption successfully
Keywords: D10; J13; 330; Corruption; Cultural Transmission; Education; Ethics; Korruption; Overlapping Generations; Theorie